2012
DOI: 10.3892/etm.2012.879
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of the correlations of mural coronary artery compression extent with myocardial bridge length and thickness evaluated by 128-slice CT

Abstract: This study aimed to investigate the correlations between the detection rate of mural coronary artery (MCA) by 128-slice CT and the MCA compression extent in systole with myocardial bridge (MB) length and thickness. A retrospective analysis was conducted for 580 patients receiving multislicespiral CT coronary angiography (MSCTCA). In addition, the MCA incidence rate and position were detected, and the MB length and thickness in the left anterior descending branch (LAD) and MCA compression extent in systole were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 19 publications
4
15
5
Order By: Relevance
“…Of note, however, a recent clinical study demonstrated a linear and positive correlation between the thickness of MBs and arterial compression as assessed on multi-detector computed tomography. 13 In conclusion, the present investigation suggests that the characteristic halo on the IVUS image of MB corresponds to muscle tissue overlying the coronary artery. Precise IVUS observations of morphologic MB properties may facilitate the accurate diagnosis of MB, providing unique pathophysiologic insights into this common anomaly as well as essential clinical information in determining the optimal treatment strategy for the patients with MB.…”
Section: Images In Cardiovascular Medicine Histology Of Ivus-detectedmentioning
confidence: 85%
“…Of note, however, a recent clinical study demonstrated a linear and positive correlation between the thickness of MBs and arterial compression as assessed on multi-detector computed tomography. 13 In conclusion, the present investigation suggests that the characteristic halo on the IVUS image of MB corresponds to muscle tissue overlying the coronary artery. Precise IVUS observations of morphologic MB properties may facilitate the accurate diagnosis of MB, providing unique pathophysiologic insights into this common anomaly as well as essential clinical information in determining the optimal treatment strategy for the patients with MB.…”
Section: Images In Cardiovascular Medicine Histology Of Ivus-detectedmentioning
confidence: 85%
“…In the study conducted by Niu et al (4), using a 128-slice CT scanner, the degree of systolic compression was calculated by the cross-sectional area method, in which the vascular area of the MB-MCA (myocardial bridge-mural coronary artery) in systole was subtracted from that during diastole, divided by the vascular area of the MB-MCA during diastole. Moreover, Liu et al, using a dual-source CT scanner, calculated the degree of the MB-MCA compression as: [(end diastolic diameter-end systolic diameter)/end diastolic diameter] × 100% (6).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, long term compression on the MB-MCA during systole leads to endothelial vessel injuries resulting from high shear stress, while the increased pressure and vortex generation in the proximal MB segment results in atherosclerosis. Moreover, in the case of deep MB, the blood perfusion is decreased in both systole and early and mid-diastole (4). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations